Proviral role of human respiratory epithelial cell‐derived small extracellular vesicles in SARS‐CoV‐2 infection. Issue 10 (22nd October 2022) - Berry, François; Morin‐Dewaele, Margot; Majidipur, Amene; Jamet, Thibaud; Bartier, Sophie; Ignjatovic, Eva; Toniutti, Donatella; Gaspar Lopes, Jeanne; Soyeux‐Porte, Pascale; Maillé, Pascale; Saldana, Carolina; Brillet, Rozenn; et al.
Abstract: Small Extracellular Vesicles (sEVs) are 50–200 nm in diameter vesicles delimited by a lipid bilayer, formed within the endosomal network or derived from the plasma membrane. They are secreted in various biological fluids, including airway nasal mucus. The goal of this work was to understand the role of sEVs present in the mucus (mu‐sEVs) produced by human nasal epithelial cells (HNECs) in SARS‐CoV‐2 infection. We show that uninfected HNECs produce mu‐sEVs containing SARS‐CoV‐2 receptor ACE2 and activated protease TMPRSS2. mu‐sEVs cleave prefusion viral Spike proteins at the S1/S2 boundary, resulting in higher proportions of prefusion S proteins exposing their receptor binding domain in an 'open' conformation, thereby facilitating receptor binding at the cell surface. We show that the role of nasal mu‐sEVs is to complete prefusion Spike priming performed by intracellular furin during viral egress from infected cells. This effect is mediated by vesicular TMPRSS2 activity, rendering SARS‐CoV‐2 virions prone to entry into target cells using the 'early', TMPRSS2‐dependent pathway instead of the 'late', cathepsin‐dependent route. These results indicate that prefusion Spike priming by mu‐sEVs in the nasal cavity plays a role in viral tropism. They also show that nasal mucus does not protect from SARS‐CoV‐2 infection, but instead facilitates it.